The preception of the community in Gentan Village Bulu Sukoharjo towards the existence of its site as a cultural heritage asset - M. Bagus Sekar Alam; Umi Yuliati; Tiwuk Kusuma Hastuti (Universitas Merdeka Malang, 2022)
The perception of Gentan Villager that is unaware and unprogressively oriented on developing the existence of the potential site as cultural heritage site and a natural tourism village (geoheritage) is a concern. The low capacity of Gentan Village human resources is a factor causing their inability to manage and optimize the existence of the site as an asset that has added economic value. The purpose of this paper is to describe the natural potential of Gentan Village, analyze the opportunities, challenges, strengths and threats in an effort to organize and develop Gentan Village as a nature-based tourism village. This paper uses a qualitative descriptive method that relies on observational data, qustionnaires and interviews with three different social classes of people in Gentan Village. The purposive technique was chosen in taking samples of three informants consisting of community leaders, tourists and local residents. The results of this study indicate that the low index of human resources of the Gentan Villager has influenced their perception on the conservation, management and utilization of cultural heritage sites. Changing the perception of Gentan Villager into a society that is aware on developing cultural heritage into a natural tourism village (geoheritage) requires the participation of many stakeholders. The conclusion of this research was the perception of Sukoharjo Gentan villager doesn’t reflect as a community who has attention to its cultural heritage and doesn’t oriented to make its village to be natural tourism destination.